Simple differentiation of Salmonella Typhi, Paratyphi and Choleraesuis from Salmonella species using the eazyplex TyphiTyper LAMP assay. Issue 6 (27th June 2020) - Rödel, Jürgen; Edel, Birgit; Braun, Sascha D.; Ehricht, Ralf; Simon, Sandra; Fruth, Angelika; Löffler, Bettina
Abstract : Introduction . Identification of typhoidal Salmonella (TS) serovars and their discrimination from non-typhoidal Salmonella (NTS) is conventionally performed by seroagglutination. This method is labour-intensive, requires technical experience and can be inconclusive in some cases. Molecular assays may be reliable alternative diagnostic tools. Aim . This study was designed to evaluate the eazyplex TyphiTyper based on loop-mediated isothermal amplification (LAMP) for fast identification of TS and S . Choleraesuis in culture. Methodology . A total of 121 Salmonella strains and 33 isolates of other Enterobacterales species were tested by the eazyplex TyphiTyper. Simulated and clinical blood cultures (BCs) were used to examine the performance of the assay for diagnosis of systemic infection. Sample preparation took about 5 min and the test running time was 20 min. Amplification was measured by real-time fluorescence detection. Results . All TS and S . Choleraesuis strains were correctly identified. The most common NTS S . Typhimurium ( n =34) and S . Enteritidis ( n =15) were detected as Salmonella species without any false positive result for TS targets. Cross-reactions of NTS with TS were only rarely observed. Direct testing of positive BCs gave correct results. Sensitivities and specificities of the assay were as follows: 100 and 99.3 % for S . Typhi, 100 and 98.7 % for S . Paratyphi A, 100 and 97.3 % for S . Paratyphi B, 100 and 100 % for S . Paratyphi C, 100 and 100 % for S . Choleraesuis, and 100 and 100 % for Salmonella species, respectively. Conclusion . The eazyplex TyphiTyper is very easy to perform and allows the rapid identification of TS and S . Choleraesuis isolates.